FORMAÇÃO DO LEITOR: OS MICROCONTOS NA SALA DE AULA - TALITA MENDES DA SILVA (2024)
This dissertation presents the results of research on the importance of reading training reflective and critical literature based on the reading of micro-stories with the target audience of the 9th year of Elementary education carried out in the classroom. This is action research that includes bibliographical survey and pedagogical intervention, developed in a didactic and employed in the reception method. This work was based on: Uses and abuses of literature inschool, by Marisa Lajolo (1982); Cultura Literada, by Marcia Abreu (2006); Walking between books: literary reading at school, by Teresa Colomer (2007); Literature: the formation of the reader: methodological alternatives, by Maria da Glória Bordini and Vera Teixeira Aguiar (1993); Literature in danger, by Todorov (2009); Literature at the center of mother tongue teaching: overcoming gaps and advancing learning, Rodrigues and Moreno (2020). We found the importance of teaching literary reading through the results achieved in workshops training, demonstrating the need to place literature at the center of teaching in mother tongue to overcome learning gaps. Keywords: reader training; literature; micro story.